Seroprevalence of dengue virus infection and its detrimental effects on pregnant women in wake of the recent floods - Mubbashir, Ayesha; Shaikh, Zain; Memon, Aaima; Alvares, Jenelle; Shahid, Ahmad (International Journal of Scientific Reports, 2023)
Dengue fever is a significant public health problem in many tropical and subtropical countries, especially those affected by severe floods as a result of global warming. The climate of these areas provides a favourable environment for the breeding vector of this disease. With Asia bearing 70% of the burden, Pakistan has been found to have a high incidence of dengue. Lack of proper healthcare facilities, rapid increase in population and substandard drainage system are a few of the problems resulting in the high number of cases. With evidence reporting the possibility of vertical transmission of this disease, it is necessary to determine the effects of dengue on the mother and the infant. Adverse effects include an increased risk of preterm birth, low birth weight, fetal loss, and maternal mortality in severe cases. The recent disastrous monsoon rainfall in Pakistan has inflicted great damage on rural areas; with the number of dengue fever cases rising to 64,000. The situation continues to worsen as the absence of proper health care and lack of action from relevant bodies has left many pregnant women vulnerable to dengue infection and unable to have safe deliveries. To combat this, the distribution of relief boxes is needed to alleviate the problems faced by victims of dengue, especially pregnant women. In order to raise awareness of this situation, this commentary has been written to describe the need for immediate action to be taken so that potential casualties of this generation and the one to come can be minimized.